The Effect of Counterpressure Massage on Reducing Pain Intensity in Active Phase I in The Working Area of Kintamani VI Health Center - Ni Made Ari Febriyanti; A.A. Santi Dewi; Luh Gede Agus Wahyu Darwati (Jurnal Genta Kebidanan, 2022)
Labor pain is a physiological condition that is experienced by almost all birthing mothers, but if it is not handled properly it will cause problems. Efforts made to reduce labor pain can use pharmacological and non-pharmacological methods. One of the efforts of non-pharmacological methods is massage counterpressure. The purpose of this study was to determine the effect of knowing counterpressure massage on reducing pain intensity during the first active phase in women giving birth. This study used a pre-experimental design with a one group pre-post test design with a sample size of 20 people. The data collection method used SOP massage counterpressure and VDS (Verbal Descriptor Scale) pain scale observation sheets and the sampling technique used was incidental sampling. Data analysis using the Wilcoxon Match Pairs test. The results of the study showed a value of p = 0.001 <0.05, so it was concluded that there was a significant difference in counterpressure massage in reducing pain in the first active phase of normal labor in the Working Area of the Kintamani VI Health Center.